Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Fiskus, dan Sanksi Perpajakan Terhadap Kepatuhan Pelaporan Wajib Pajak - Rianty, Martha; Syahputepa, Riza (Balance : Jurnal Akuntansi dan Bisnis, 2020)
This research was conducted in connection with the ongoing tax payment period, namely March for Personal WP and April for Entities. The location of the study was conducted at KPP Pratama Seberang Ulu Palembang with a sample of 100 people taken based on the Slovin method. The independent variable in this study is the awareness of taxpayers, the quality of tax authorities, tax sanctions, while the dependent variable is taxpayer reporting compliance. The sample used is taxpayers who are registered at KPP Seberang Ulu Palembang. The results showed that the variable awareness of taxpayers and tax penalties had a significant positive effect on taxpayer compliance, and the variable Fiscus Services did not affect the compliance of taxpayers registered at the Seberang Ulu KPP. The results of this study are expected to provide input to improve service and satisfaction of taxpayers especially in the city of Palembang.